Pengaruh Brand Image, Promotion dan Electronic Word of Mouth terhadap Intention to Buy Product Pada Aplikasi Belanja Online - Farley Dharmawan; Erna Sofriana Imaningsih (Journal of Fundamental Management (JFM), 2021)
The research aims to identity the influence of Brand Image, Promotion and Electronic Word of Mouth on Shopee.co.id application users. The subjects in this study were consumer who used the Shopee.co.id application in buy product. The sample used in this study was 150 respondents. The sampling technique using a convenience sampling. By using quantitative descriptive approach. Therefore, the analysis of the data used is the statistical analysis in the form of SEM-PLS. The results of this study showed Brand Image has a significant positive effect on the Intention to Buy Product. Promotion have none significant effect on the Intention to Buy Product and Electronic Word of Mouth has a significant positive effect on the Intention to Buy Product.Keyword : Brand Image, Promotion, Electric Word of Mouth, Intention to Buy Product, Shopee.co.id application